Konsekuensi Hukum Persekongkolan Tender Terhadap Kontrak Pengadaan Barang dan Jasa Pemerintah - Yulius Efendi; Teguh Wicaksono (Perspektif Administrasi Publik dan hukum, 2025)
Competition between business actors can occur unfairly by colluding between business actors or with other parties, thus harming consumers and even state finances. With the occurrence of tender collusion, there is a conspiracy, lying behavior or an unlawful act by violating a government procurement mechanism, so that it has an impact on the government procurement contract made between business actors and the tender committee related to the validity and legal consequences of the implementation of the government procurement contract. In the provisions of the procurement of goods and services, if the parties commit a tender collusion, administrative sanctions will be imposed on the parties if proven, through civil dispute resolution. This means that the government procurement contract and services remain valid and binding on the parties, and cannot be terminated unilaterally by the organizing committee. This study uses a legal document approach. In various cases of tender collusion in the procurement of goods and services, the parties involved are processed criminally by law enforcement, but the procurement contracts for goods and services that have been made previously remain valid and are continued until completion, so it is necessary to conduct a legal analysis related to the status of the validity of the contract in tender collusion.